A survey of multivitamin supplement knowledge, attitude, and use in the urban community of Bikaner, Rajasthan - Savita Saini; Najmul Hasan (Wolters Kluwer Medknow Publications, 2015)
Background and Objective: Over the last two decades, there has been a trend for people to supplement their nutritional intake with dietary supplements including multivitamins, which are also commonly prescribed as a concomitant medication. We conducted a community-based survey in an urban population to assess consumers' knowledge, practices, and attitudes regarding multivitamin supplements. Materials and Methods: A cross-sectional questionnaire-based survey was conducted from November 2013 to April 2014 among 500 participants residing in urban areas of Bikaner (Rajasthan). The data were collected in a predesigned questionnaire after obtaining written informed consent from each participant. Results: The survey results showed that the taking of multivitamin supplements is quite prevalent (64.2%) in the community of urban areas of Bikaner. Physicians were found to be the most common source of information regarding multivitamins; however, consumers do get the information from the internet, newspaper, and relatives also. Multiple reasons were quoted for the practice of multivitamins such as maintenance of general health, compensation for the deficiencies, etc. The majority of the respondents were unaware of the correct indications for use of vitamin supplements and had little knowledge of harmful effects. Conclusion: This survey in an urban population highlights that the multivitamin supplements are commonly taken on a daily basis. Most consumers are unaware of any possible side-effects or drug-supplement interactions. There is a continuing need to adopt certain educational interventions for physicians to update and disseminate knowledge of vitamin supplements to their patients and also to increase awareness regarding their correct usage.